Enhancing PPE Awareness through SAFE Education among Manufacturing Workers in Sleman, Indonesia - Alifah Muti Husna; Haris Setyawan; Nabylla Sharfina Sekar Nurriwanti (Universitas Airlangga, 2025)
Introduction: Indonesia's growing infrastructure development increases the demand for precast concrete, which also increases workplace accidents due to the low safety awareness in PPE use. Audio media for safety education is considered an effective method to increase safety awareness on-site. This research aimed to examine the effects of SAFE education on enhancing safety awareness regarding the use of PPE. Methods: A quasi-experimental study was conducted with a total sample of 70 workers, divided into an Intervention Group (n=35) who received the SAFE (Sounding Awareness For Everyone) program and a Control Group (n=35) who received no intervention. The subjects received a 5-minute audio message on safety and PPE use, delivered over 14 consecutive days. The data on knowledge, attitude, and action were collected using a validated 45-item questionnaire and analyzed with the Wilcoxon and Mann-Whitney tests in SPSS 25. Results: Significant improvements were evident in knowledge, attitude, and action regarding the use of PPE among subjects in the intervention group. The mean knowledge score increased from 32.89 to 50.91, the attitude score increased from 31.20 to 49.17, and the action score increased from 30.34 to 48.71; all showed p < 0.001. Meanwhile, the control group showed no significant differences in mean scores before and after the intervention (p > 0.05). The Mann-Whitney test also showed significant differences between the intervention and control groups in post-test results (p < 0.001). Conclusion: Sounding Awareness For Everyone (SAFE) education was effective in improving safety awareness regarding PPE use among production workers at PT X.